Understanding and leveraging mechanical forces in haemostasis - Macleod Briongos, Iain, author; Bark, David, advisor; Olver, Christine, committee member; Popat, Ketul, committee member; Henry, Charles, committee member (Colorado State University. Libraries, 2023)
Cardiovascular disease accounts for one third of deaths worldwide, of which over 75% are in low- and middle-income countries. Platelets and von Willebrand Factor play a central role in haemostasis and in cardiovascular diseases, being involved in both excess clotting that causes heart attacks and strokes, and excess bleeding. Herein, we outline a method for leveraging paper microfluidics with the aim of developing a WHO ASSURED criteria compliant point-of-care device for the diagnosis of von Willebrand Disease, as well as work to increase the understanding of mechanical force generation by platelets through Traction Force Microscopy.
Keywords: microfluidics; TFM; VWF; platelets; biomechanics; VWD